PELATIHAN PENULISAN BUKU REFERENSI BAGI GURU SEKOLAH DASAR SEBAGAI UPAYA PENINGKATAN BUDAYA LITERASI - Rukin, Rukin (LPPM Universitas Nusa Mandiri, 2025)
The dynamic development of the education sector requires teachers who are highly motivated and skilled in adapting to technological advancements. One effective strategy for elementary school teachers is to develop engaging, student-centered, and environmentally contextual learning materials. To support this, higher education institutions play a vital role in offering direction, encouragement, and mentoring through community service programs. This initiative aimed to enhance the competencies of teachers at SD Arjowinangun 2 and SDN Polehan 5 in Malang City by equipping them with the skills and independence to write reference books that support classroom learning. The program combined independent mentoring and classical in-school training, implemented over three months, with a two-day intensive session on August 7–8, 2024, followed by post-training mentoring. Teachers received detailed guidance on drafting, structuring, and publishing reference books. Throughout the sessions, participants engaged in active discussions to address challenges in the writing process. As a result, teachers successfully produced reference books tailored to the needs of their students, contributing to the availability of contextual learning resources and the overall improvement of instructional quality in elementary education in SD Arjowinangun 2 and SDN Polehan 5 in Malang City in supporting the learning process.